Multiple clinical profiles of families with the short QT syndrome. Issue Volume 20:Issue FI 1(2018) (19th July 2017) - Akdis, D; Saguner, A M; Medeiros-Domingo, A; Schaller, A; Balmer, C; Steffel, J; Brunckhorst, C; Duru, F
Abstract: Aims: Short QT syndrome (SQTS) is a rare cardiac channelopathy characterized by a shortened corrected QT (QTc)-interval that can lead to ventricular arrhythmias and sudden cardiac death. The aim of this study was to investigate the clinical phenotypes and long-term outcomes of three families harbouring genetic mutations associated with the SQTS. Methods and results: Clinical data included medical history, physical examination, 12-lead ECG, 24-h Holter-ECG, and transthoracic echocardiography from three index patients and their first-degree relatives. Next generation clinical exome sequencing and genetic cascade screening were performed in index patients and their relatives, respectively. Two index patients experienced malignant ventricular arrhythmias and one patient suffered from arrhythmogenic syncope during a median follow-up period of 8 years. They all had genetic mutations associated with the SQTS. Two mutations were found in the KCNH2 gene, and one in the CACNA2D gene. One patient had an additional SCN10A variant. Alive and mutation-positive family members had short QTc-intervals, but no further phenotypic manifestations. None of the mutation-negative family members had an abnormal ECG or any symptoms. In all patients with shortened QTc-intervals, the QTc-interval had a low long-term variability and QTc shortening always remained detectable by 12-lead ECG. Conclusion: This study shows the variety of phenotypic manifestations in different families with SQTS. It further emphasizes the importance of a 12-lead ECG for early diagnosis, and the utility of next generation sequencing for the identification of mutations associated with the SQTS.